AB0577 ENDOTHELIAL DYSFUNCTION AND ATHEROSCLEROSIS IN SYSTEMIC SCLEROSIS: A MULTIPARAMETRIC ANALYSIS USING IMAGING TECHNIQUE AND LABORATORY MARKERS OF INFLAMMATION AND VASCULAR FUNCTION: SCLERODERMA CV RISK STUDY. (13th June 2020) - Garg, N.; Syngle, A.; Gera, D.; Kaur, S.
Abstract : Background: Systemic sclerosis (SSc) patients have an increased risk for atherosclerotic cardiovascular disease (CVD), possibly mediated by inflammatory and fibrotic mechanisms 1 . However, pathogenesis of accelerated atherosclerosis in SSc remains to be elucidated. Endothelial dysfunction is the key initial event in atherosclerosis. Predictors for rapid evolution of cardiovascular complications would be highly desirable for CV risk stratification. This study aims to assess endothelial function and atherosclerosis in SSc, in context of markers of inflammation and vascular function in SSc patients. Objectives: To assess endothelial function and atherosclerosis in SSc in context of markers of inflammation and vascular function in SSc patients. Methods: A cross-sectional study was performed in 20 SSc patients meeting the 2013 European League Against Rheumatism (EULAR) and American College of Rheumatology (ACR) classification criteria and 18 healthy controls matched for age and sex. Flow-mediated dilatation (FMD) assessed by AngioDefender and CIMT measured ultrasonographically. Disease-specific measures included: Disease duration, Modified Rodnan Skin Score (mRSS), EUSTAR activity score in SSc. We also assayed markers of inflammation, including C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), proinflammatory cytokines (interleukin IL-1, IL-6, and IL-17), and endothelial dysfunction including lipids, serum nitrite and TBARS (marker of oxidative stress). Quality of life measured by Scleroderma Health Assessment Questionnaire (SHAQ). Results: FMD is significantly lower in SSc patients compared with controls (6.13±0.35% vs. 9.12±0.25%, p≤0.05). CIMT is significantly higher in SSc patients compared with controls (0.071±0.04cm vs. 0.035±0.02cm p≤0.05). Compared with controls, SSc patients had significantly (p≤0.05) elevated mRSS, EUSTAR score, ESR, CRP, IL-1, IL-6, IL-17, nitrite, TBARS and SHAQ whereas HDL levels are significantly reduced in SSc compared with controls (p≤0.05). In SSc, FMD inversely correlated with EUSTAR score, mRSS, IL-6 (Fig. 1A ), serum nitrite (Fig. 1B ), TBARS (Fig. 1C ) and CIMT (Fig. 1D ). CIMT positively correlated with age (Fig. 2A ), disease duration, CRP (Fig. 2B ) and IL-17 (Fig. 2C ) and inversely correlated with HDL (Fig. 2D ) (p< 0.05). Conclusion: In the present study, FMD and CIMT are impaired in SSc, indicating endothelial dysfunction and accelerated atherosclerosis, respectively. EUSTAR score, mRSS, IL-6, serum nitrite, CIMT and TBARS predicted endothelial dysfunction. Age, disease duration, CRP, IL-17, HDL and impaired FMD predicted accelerated atherosclerosis. SSc-related inflammatory mechanisms (IL-6, IL-17) and markers of vascular function (CRP, serum nitrite and TBARS) may all be involved in the development of vascular disease in SSc. Cytokine-triggered inflammation mediated by nitrite and TBARS is associated with endothelial dysfunction and accelerated atherosclerosis in SSc. These markers would possibly serve as predictors of endothelial dysfunction and atherosclerosis and more importantly therapeutic targets to prevent premature atherosclerosis and cardiovascular disease in SSc. References: [1]Pagkopoulou E, Poutakidou M, Garyfallos A, Kitas G, Dimitroulas T. Cardiovascular risk in systemic sclerosis: Micro- and Macro-vascular involvement. Indian Journal of Rheumatology 2017;12:S211-7. Acknowledgments: None Disclosure of Interests: None declared